2019
DOI: 10.7150/thno.34509
|View full text |Cite
|
Sign up to set email alerts
|

Research tools for extrapolating the disposition and pharmacokinetics of nanomaterials from preclinical animals to humans

Abstract: A critical step in the translational science of nanomaterials from preclinical animal studies to humans is the comprehensive investigation of their disposition (or ADME) and pharmacokinetic behaviours. Disposition and pharmacokinetic data are ideally collected in different animal species (rodent and nonrodent), at different dose levels, and following multiple administrations. These data are used to assess the systemic exposure and effect to nanomaterials, primary determinants of their potential toxicity and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 120 publications
(238 reference statements)
1
16
0
Order By: Relevance
“…115 It also provides a more conservative dose estimate, especially for nanomaterials. 116 Generally, the body surface area seems to have a good correlation among species with several parameters including oxygen utilization, caloric expenditure, basal metabolism, blood volume, and circulating plasma protein. 37,117 Valic and Zheng 116 mentioned that the clinical starting dose may be determined by dividing the estimated human equivalent dose (HED) of the rodent by a safety factor with a default value of 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…115 It also provides a more conservative dose estimate, especially for nanomaterials. 116 Generally, the body surface area seems to have a good correlation among species with several parameters including oxygen utilization, caloric expenditure, basal metabolism, blood volume, and circulating plasma protein. 37,117 Valic and Zheng 116 mentioned that the clinical starting dose may be determined by dividing the estimated human equivalent dose (HED) of the rodent by a safety factor with a default value of 10.…”
Section: Discussionmentioning
confidence: 99%
“…116 Generally, the body surface area seems to have a good correlation among species with several parameters including oxygen utilization, caloric expenditure, basal metabolism, blood volume, and circulating plasma protein. 37,117 Valic and Zheng 116 mentioned that the clinical starting dose may be determined by dividing the estimated human equivalent dose (HED) of the rodent by a safety factor with a default value of 10. The safety factor allows variability in extrapolating from animal toxicity studies in humans resulting from uncertainties due to enhanced sensitivity to pharmacologic activity in humans versus animals, difficulties in detecting certain pathologies in animals (eg, headache, myalgia, and mental disturbances), differences in receptor densities or affinities, and unexpected toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that the dose conversion from animal to human studies is one of the most controversial areas in clinical pharmacology were understanding the concept of extrapolation of dose between species is important for pharmaceutical researchers [ 54 , 55 ]. Also, it was reported that the extrapolating nanomaterials disposition and pharmacokinetics from preclinical animal models to humans will hopefully result in a more straightforward roadmap for the clinical translation of promising nanomaterials [ 56 ]. In this concern, several equations were used to calculate the human equivalent dose (HED); most commonly was that related to body weight [ 55 ] as follows: …”
Section: Discussionmentioning
confidence: 99%
“…In bringing forward nBIC-TAF to non-human primates (NHP) testing, as the best animal model for HIV therapy/PrEP preclinical assessments, many unknowns surround the choice of the NHP regimen. Nanoformulated drugs have a high degree of pharmacokinetic unpredictability when scaled from smaller to higher species, and therefore it can be inappropriate to use standard interspecies scaling rules for nanoformulated drugs (Valic and Zheng, 2019). Additionally, NHP experiments are costly and beg ethical concerns, thus doseescalation assessments in NHP could become burdensome.…”
Section: Introductionmentioning
confidence: 99%